Fãs organizacionais e a memória no relacionamento com as organizações – um estudo do Canal Viva - Parada, Augusto Rodrigues (Universidade do Vale do Rio dos Sinos, 2015)
This thesis seeks, in the first place, to understand the relational space established between organizations and their audiences in environments of shared knowledge on the World Wide Web. By establishing the parameters about the publics of an organization from a perspective of power, an assumption of public was developed, which was called organizational fan. The same reinforces the guidelines identified in cultural fans, especially with regard to socialization precepts and the sharing of symbolic goods. From this perspective, the memory-element is highlighted, as understood as one of these symbolic constituents to be shared by the fans, reinforce feelings of identification and identity of the public and organizations. The object of study of this thesis is the Canal Viva– broadcaster that is part of the Grupo Globo, whose raw material of its products is memory itself. By using the Grounded Theory as a methodological north, the platforms of Canal Viva on the Internet were analyzed and divided into three movements: Facebook, Portal and Parallel Content. The conversations of the public in these three environments were categorized and analyzed so that at the end of the thesis, we could present a new dimension of public (organizational fan), whose behavior in these environments indicates a predisposition to socialize and share symbolic goods, and in the case of our object, the memory (individual, collective and also organizational) appears as a promising relational element to be explored in organizational communication.
Keywords: Fãs; Públicos; Comunicação organizacional; Fandoms; Memória; Fans; Public; Organizational communication; Memory; ACCNPQ::Ciências Sociais Aplicadas::Comunicação